2005
DOI: 10.2746/0425164054406829
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intra‐articular drilling and diode laser treatment for arthrodesis of the distal tarsal joints in normal horses

Abstract: Summary Reasons for performing study: Anecdotal reports suggest that laser‐facilitated arthrodesis of the distal tarsal joints improves the prognosis compared with intra‐articular drilling but no objective comparisons have been performed. Objectives: To evaluate intra‐articular drilling and laser‐facilitated arthrodesis using in situ and in vivo techniques. Methods: Fourteen cadaver limbs were evaluated in situ for chondrocyte viability after both surgical techniques. In vivo, one randomly selected limb was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…1988), screws and/or a ‘T’‐plate (Wyn‐Jones and May 1986; Auer 1992). Arthrodesis with diode laser has also been described (Scruton et al . 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1988), screws and/or a ‘T’‐plate (Wyn‐Jones and May 1986; Auer 1992). Arthrodesis with diode laser has also been described (Scruton et al . 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Other treatments include a variety of methods to arthrodese the joints such as drilling to remove cartilage (Adams 1970;Edwards 1982), drilling combined with implants such as stainless steel transfixion pins (Mackay and Liddell 1972), stainless steel baskets containing autogenous cancellous bone grafts (Archer et al 1988), screws and/or a 'T'-plate (Wyn-Jones and May 1986;Auer 1992). Arthrodesis with diode laser has also been described (Scruton et al 2005). Other techniques include subchondral fenestration to relieve the increased pressure in the distal tarsal bones (Sonnichsen and Svalastoga 1985) and partial neurectomy of the tibial and neurectomy of deep peroneal nerves (Imschoot et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental studies on the use of a laser for facilitated ankylosis of the distal tarsal joints have confirmed some degree of cartilage destruction post lasing, though neither experimental study confirmed solid bony fusion 12,21 . Without a nonlased control group in a prospective randomized clinical trial, it is impossible to know to what degree the laser‐induced loss of remaining articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographic scales can be either qualitative or quantitative. A quantitative scale attributes a numeric score to radiographic abnormalities according to their perceived severity 13 . In a study of equine distal limb arthrodesis, a dichotomous rating scale was proposed according to the presence of radiographic changes 14 .…”
Section: Discussionmentioning
confidence: 99%
“…A quantitative scale attributes a numeric score to radiographic abnormalities according to their perceived severity. 13 In a study of equine distal limb arthrodesis, a dichotomous rating scale was proposed according to the presence of radiographic changes. 14 When assessing an ab-normal radiographic sign in terms of presence or absence of the lesion, there is a very high accuracy and agreement between observers.…”
Section: Discussionmentioning
confidence: 99%